Ultradispersed Mo/TiO2 catalysts for CO2 hydrogenation to methanol. Issue 18 (2nd September 2021) - Len, Thomas; Bahri, Mounib; Ersen, Ovidiu; Lefkir, Yaya; Cardenas, Luis; Villar-Garcia, Ignacio J.; Pérez Dieste, Virginia; Llorca, Jordi; Perret, Noémie; Checa, Ruben; Puzenat, Eric; Afanasiev, Pavel; et al.
Abstract : Molybdenum species highly dispersed on selected titania materials catalyse CO2 hydrogenation to methanol. Abstract : Mo/TiO2 catalysts with atomic dispersion of molybdenum appear active and stable in the gas-phase hydrogenation of CO2 . A comparison between various titania materials shows a crucial effect of the support surface structure on the methanol yield. Molybdenum supported at low coverage on rutile titania nanorods is the most active and methanol-selective system. From catalyst characterization by aberration-corrected scanning transmission electron microscopy, near-ambient pressure X-ray photoelectron spectroscopy, diffuse reflectance UV-vis spectroscopy, and temperature-programmed techniques, we suggest that the most active catalysts for methanol production involve ultradispersed molybdate species with high reducibility and strong interaction with the rutile support.